Isolation and structural characterisation of rhodium(iii) η2-fluoroarene complexes: experimental verification of predicted regioselectivity. Issue 18 (21st April 2020) - Gyton, Matthew R.; Kynman, Amy E.; Leforestier, Baptiste; Gallo, Angelo; Lewandowski, Józef R.; Chaplin, Adrian B.
Abstract : Well defined rhodium complexes for probing the coordination site preference of partially fluorinated benzenes. Abstract : The isolation and solid-state characterisation of complexes featuring partially coordinated benzene, fluorobenzene and all three isomers of difluorobenzene are described. Supported by a DFT analysis, this well-defined homologous series demonstrates the preference for η 2 -coordination of fluoroarenes via the HCCH sites adjacent to a fluorine substituent.